Age and sex differences in the efficacy of early invasive strategy for non-ST-elevation acute coronary syndrome: A comparative analysis in stable patients - Cenko, Edina; Bergami, Maria; Yoon, Jinsung; Vadalà, Giuseppe; Kedev, Sashko; Kostov, Jorgo; Vavlukis, Marija; Vraynko, Elif; Miličić, Davor; Vasiljevic, Zorana; Zdravkovic, Marija; Galassi, Alfredo R.; et al. (Elsevier BV, 2025)
Objective: Previous works have struggled to clearly define sex-specific outcomes based on initial management in NSTE-ACS patients. We examined whether early revascularization (<24 h) versus conservative strategy impacts differently based on sex and age in stable NSTE-ACS patients upon hospital admission. Methods: We identified 8905 patients with diagnosis of non-ST elevation acute coronary syndromes (NSTE-ACS) in the ISACS-TC database. Patients with cardiac arrest, hemodynamic instability, and serious ventricular arrhythmias were excluded. The final cohort consisted of 7589 patients. The characteristics between groups were adjusted using inverse probability of treatment weighting models. Primary outcome measure was all-cause 30-day mortality. Risk ratios (RRs) with their 95 % CIs were employed. Results: Of the 7589 NSTE-ACS patients identified, 2450 (32.3 %) were women. The data show a notable reduction in mortality for the older women (aged 65 years and older) undergoing early invasive strategy compared to those receiving an initial conservative (3.0 % versus 5.1 %; RR: 0.57; 95 % CI: 0.32 - 0.99) Conversely, younger women did not exhibit a significant association between early invasive strategy and mortality reduction (2.0 % versus 0.9 %; RR: 2.27; 95 % CI: 0.73 - 7.04). For men, age stratification did not markedly alter the observed benefits of an early invasive strategy over a conservative approach in the overall population, with reduced death rates in both older (3.1 % versus 5.7 %; RR: 0.52; 95 % CI: 0.34 - 0.80) and younger age groups (0.8 % versus 1.7 %; RR: 0.46; 95 % CI: 0.22 - 0.94). These age and sex-specific mortality patterns did not significantly change within subgroups stratified by the presence of NSTEMI or a GRACE risk score>140. Conclusion: Early coronary revascularization is associated with improved 30-day survival in older men and women and younger men who present to the hospital in stable conditions after NSTE-ACS. It does not confer a survival advantage in young women. Further studies are needed to more accurately risk-stratify young women to guide treatment strategies.
Keywords: Mortality; NSTE-ACS; Revascularization; Risk stratification; Women